ACCESS TO LEARNING MATERIALS AND RESOURCES - Sharifova Barno Ravshanzoda, Gazieva Saida Turgunovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
Access to learning materials and resources plays a crucial role in the quality of education students receive. With the development of digital tools and increasing connectivity, learners now have more opportunities than ever to access knowledge, irrespective of their geographical location. This article investigates the importance of equitable access to educational resources, including textbooks, digital platforms, libraries, and open-source materials. The study emphasizes the benefits of enhanced accessibility and highlights the barriers that still hinder equal access for all students.